Infectious Diseases Consultation Is Associated With Decreased Mortality in Enterococcal Bloodstream Infections. (19th February 2020) - Lee, Rachael A; Vo, Daniel T; Zurko, Joanna C; Griffin, Russell L; Rodriguez, J Martin; Camins, Bernard C
Abstract: Background: Enterococcus species frequently cause health care–associated bacteremia, with high attributable mortality. The benefit of consultation with infectious disease (ID) specialists has been previously illustrated with Staphylococcus aureus bacteremia. Whether ID consultation (IDC) improves mortality in enterococcal bacteremia is unknown. Methods: This is a retrospective cohort single-center study from January 1, 2015, to June 30, 2016, that included all patients >18 years of age admitted with a first episode of Enterococcus bacteremia. Patients were excluded if death or transfer to palliative care occurred within 2 days of positive blood culture. Results: Two hundred five patients were included in the study, of whom 64% received IDC. Participants who received IDC were more likely to undergo repeat cultures to ensure clearance (99% vs 74%; P < .001), echocardiography (79% vs 45%; P < .001), surgical intervention (20% vs 7%; P = 0.01), and have appropriate antibiotic duration (90% vs 46%; P < .001). Thirty-day mortality was significantly higher in the no-IDC group (27 % vs 12 %; P < .007). In multivariate analysis, 30-day in-hospital mortality was associated with both E. faecium bacteremia (adjusted odds ratio [aOR], 2.39; 95% confidence interval [CI], 1.09–5.23) and IDC (aOR, 0.35; 95% CI, 0.16–0.76). Conclusions: Patients who received IDC for Enterococcus bacteremia had significantly lower 30-day mortality. Further prospective studies are necessary to determine if these outcomes can be validated in other institutions for patients who receive IDC with Enterococcus bacteremia. Abstract : We report a retrospective cohort study of the effect of infectious diseases consultation (IDC) on thirty-day mortality in patients with Enterococcus bacteremia. We found a 65% decrease in 30-day in-hospital mortality, illustrating that IDC may be essential in improving survival.